2015
DOI: 10.1590/0037-8682-0233-2014
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii seropositivity and risk factors in pregnant women followed up by the Family Health Strategy

Abstract: Introduction:Toxoplasmosis is a zoonotic infection caused by Toxoplasma gondii. It is transmitted by the ingestion of contaminated water and foods, by soil contaminated with cat feces, especially while handling it, and congenitally via the placenta. The diagnosis of maternal infection is made by serological detection of either IgM or IgG antibodies. This study assessed the seropositivity in pregnant women followed up by the Family Health Strategy (FHS) in Lages, Santa Catarina, Brazil. Methods:The study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
5
0
6
Order By: Relevance
“…53 No Brasil, a prevalência de infecção por T. gondii em humanos é especialmente alta e pode chegar a 100% em algumas áreas e em média 60% das mulheres adultas já foram expostas a este protozoário. [54][55][56] Felídeos geralmente são considerados fontes primárias de infecção e hospedeiros definitivos, adquirindo o protozoário através da ingestão de carne ou fezes contaminadas. Inúmeros hospedeiros intermediários podem disseminar a doença, ou o parasito entre eles, consumindo a carne de outros indivíduos infectados.…”
Section: Toxoplasma Gondiiunclassified
“…53 No Brasil, a prevalência de infecção por T. gondii em humanos é especialmente alta e pode chegar a 100% em algumas áreas e em média 60% das mulheres adultas já foram expostas a este protozoário. [54][55][56] Felídeos geralmente são considerados fontes primárias de infecção e hospedeiros definitivos, adquirindo o protozoário através da ingestão de carne ou fezes contaminadas. Inúmeros hospedeiros intermediários podem disseminar a doença, ou o parasito entre eles, consumindo a carne de outros indivíduos infectados.…”
Section: Toxoplasma Gondiiunclassified
“…However, both studies did not test for IgM antibodies. In Brazil, the prevalence of Toxplasma IgG was 16% among pregnant women while that of IgM was 1% in the same population (de Quadros et al, 2015). Moreover, in an Ethiopian study, the seroprevalence was found to be 60% and 64% in females and males respectively (Negash et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Infection by this parasite in humans may occur through water and foods contaminated by oocysts, or it may be congenital, when the pregnant woman becomes contaminated during pregnancy and the etiologic agent crosses the placental barrier. 1,2 It is estimated that 1/3 of the world population is infected, but prevalence varies in different regions. In Brazil, seroprevalence varies between 42% and 90% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of fetal infection is higher when the disease is acquired in the third trimester compared with the first trimester, but the severity of the involvement is greater when maternal infection occurs in the first trimester. 1,3,[9][10][11][12] In pregnant women with exams that suggest acute infection, it is necessary to determine whether there is any impairment to the fetus. In these situations, one can perform amniocentesis to detect the presence of the parasite's DNA in the amniotic fluid through the polymerase chain reaction (PCR) method.…”
Section: Introductionmentioning
confidence: 99%